KNOWLEDGE ATTITUDE AND PRACTICE OF REPRODUCTIVE HEALTH CARE BETWEEN GENERATIONS AND ITS EFFECT ON RAJONIVRITHI - mole, *S. Shahina; Nalinakshan, A. (International Journal of Ayurveda and Pharma Research, 2017)
Menopause is a normal, natural and inevitable phenomenon in a female life. It is a part of ageing. Most women will experience some symptoms around the menopause. The duration and severity of these symptoms varies from woman to woman. Rajonivrithi kala has been mentioned as 50 years in a female by almost all Ayurveda acharyas. But not mention any symptoms or health problems specially related to this transitional period. Nidana of Rajonivrithi is assigned to the factors like Jara, Kala, Swabhava, Vayu, Dhatukshaya and Karma. It is the Sandhikala of Youvanakala and Vardhakyakala. This is the transitional period of Dosha predominance from Pitta to Vata. At this stage alteration in the physiological activities of Pitta dosha and association of increase in Vatha dosha leads to hot flushes and other symptoms of menopause ie menopausal symptoms. Rajonivrithi lakshanas are not mentioned in our classical texts as such. What is the reason of avoiding menopausal symptoms or Aarthava virama vikaras from all Ayurvedic classics? There is a chance that menopausal period was comparatively uneventful in the previous generation when compare to present generation. This characters or change in response can be attributed to the regular practice of Ayurvedic life style, and traditional reproductive health care practice (including Rajaswalacharya Garbhinicharya & Soothikacharya). Garbhinicharya & Soothikacharya are commonly practiced by new generation up to an extent. But practicing of Rajaswalacharya is uncommon. To find out whether any relation between the reproductive life care and menopausal symptoms we conduct a survey among patients coming in the center with menopausal ailments. In survey it was observed that the Rajaswala charya was more prevalent in the older generation when compared to the present generation, and this might have contributed to a healthier menopausal period, in the older generations.